Sciatic nerve entrapment causing posterior knee pain - Zainol Fithri, Zairul Nizam; M. H., Shukor (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2005)
We report a case of sciatic nerve entrapment resulting in a patient experiencing pain over the posterior aspect of the knee, simulating a Baker’s cysts. Surgical exploration revealed a tight fibrous arch compressing the distal portion of the complete relief of symptoms. This form of presentation is rate and should be considered as a differential diagnosis when a patient presents with complaints of pain in the back of then knee.